ANALISA PEMELIHARAAN INFANT WARMER DI RUMAH SAKIT UMUM SARAH MEDAN - M. Wahid Afdillah; Dzia Ur Ridha (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2018)
Infant warmer is one of the live support and saving tools that is used to provide comfort and warmth to newborns, where the baby needs a temperature that is in accordance with the temperature in the mother's womb, which is between 34 °C - 37 °C. The purpose of this study was to determine the implementation of the maintenance of the Infant Warmer at Sarah General Hospital Medan. This research was conducted at Sarah General Hospital Medan Jl. Baja Raya No.10, Kec. Medan Baru by distributing questionnaires containing questions/statements. The type of research used is a descriptive method which was carried out from January 2018. The results obtained from the respondents, from 22 questionnaires there were 21 questionnaires answered Yes and 1 questionnaire answered No. It was concluded that the implementation of the maintenance of the Infant Warmer at Sarah Medan General Hospital was running properly, and was declared good.